Solvency Ratio Analysis to Assess Financial Performance in Insurance Companies: Case Study PT. Taspen Life Insurance - Anita Sumartinih (CV. Publikasi Indonesia, 2024)
Assessing a company's financial performance is a very important thing to do. Financial performance assessment can also show the extent of the company's success in achieving its goals. The research object focuses on the problem of solvency ratio analysis to assess financial performance in the case study insurance company PT. Taspen Life Insurance. PT. Taspen Life Insurance is a subsidiary of PT TASPEN (Persero) with 99.97% share ownership and 0.03% shares owned by the Taspen Jakarta Employees Cooperative. Taspen Life provides a variety of group and individual life insurance product solutions that have the benefits of life protection, future and old age planning, education funds, and critical illness insurance. This research aims to determine the company's performance assessment through analysis of the solvency ratio at PT. Taspen Life Insurance. The subject of this research is PT. Taspen Life Insurance. The method used in this research is the analytical descriptive method. The type of data used is secondary data obtained from the PT company performance report website. Taspen Life Insurance in 2018, 2019, 2020, 2021, 2022. Based on the results of the study, the analysis of the solvency ratio on PT. Taspen Life Insurance in 2018, 2019, 2020, and 2022 is considered to have poor financial performance because its solvency level exceeds 200%. In 2021, the achievement of the solvency ratio of PT. Taspen Life Insurance is less than 200%, which can be interpreted as the financial performance of PT. Taspen Life Insurance in 2021 is considered quite good.